Levels of Parental Drinking in the Presence of Children: An Exploration of Attitudinal Correlates. (4th November 2021) - Bowden, Jacqueline A; Delfabbro, Paul; Room, Robin; Miller, Caroline L; Wilson, Carlene
Abstract: Aims: This study aimed to examine perceived social norms, the effect of parental drinking on these norms, alcohol use in front of children, and how norms and consumption vary based on child age and gender of the parent. Methods: A cross-sectional online panel survey was undertaken with n = 1000 Australian adults (including 670 parents) aged 18–59 years. The survey assessed: alcohol consumption in front of children; normative attitudes towards drinking in the presence of children; and perceived social norms. Results: Overall, 33.9% of parents reported drinking a glass of alcohol each day or a couple of times a week, 18.2% reported getting slightly drunk and 7.8% indicated getting visibly drunk each day or a couple of times a week with their children present. In total, 37.5% reported drinking in front of their children at least weekly. Fathers were more likely to drink in front of children than mothers. Most parents deemed drinking small amounts of alcohol in front of children as acceptable but did not accept drunkenness. Respondents were less concerned about a father drinking one or two drinks in front of their children than a mother. Social expectations were not related to child age, but norms related to others' perceived behaviour were. Conclusions: Many parents, particularly fathers consume alcohol in front of their children. There is a need to target health promotion strategies to adults and parents consuming in excess of health guidelines, and to the many parents who are consuming alcohol at higher levels in front of their children. Abstract : Short Summary: This study examined perceived social norms and alcohol use in front of children among Australian adults. Many parents are consuming alcohol in front of their children, particularly fathers. Moderate parental drinking in front of children was considered acceptable but drunkenness was not.